E.P. Meinecke and the Development of the Modern Auto Campground - Terence Young (IdeAs)
Recreational camping began in the United States in the 1860s after the conclusion of the American Civil War. It was an antimodern response to the rapid industrialization and urbanization that had begun to sweep through America. Americans embraced many of modernity’s positive aspects, but they were uncomfortable with and worn down by the urban noise, pollution and many other negative characteristics that also came along. Camping emerged as a form of leisure-time pilgrimage to sacred nature in order to regenerate America’s tired urban dwellers. Ironically, camping is not beyond the reach of modernity despite its antimodern roots. Camping’s technology, practices, spaces and management have been shaped by the same modernizing forces that led to America’s urban-industrial life. As the modern automobile became a central part of the camping experience during the 1920s, the number of campers increased dramatically causing the nature in and around public automobile campgrounds to deteriorate rapidly. The most widely embraced solution to this problem was created by E.P. Meinecke. A plant pathologist in the U.S. Department of Agriculture, he developed a modern version of the automobile campground that retained many of the antimodern elements sought by campers. Meinecke’s design became the standard for U.S. national parks and forests.